PENGARUH SEMANGAT KERJA, GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN BARRU - Safirah Syihab; Mashur Razak; Muhammad Hidayat (AkMen JURNAL ILMIAH, 2020)
The research aims to determine and analyze the influence of work spirit, leadership style, and work motivation on the performance of the employees of Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Barru. This type of research is quantitative research with survey methods. This research was conducted at the Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Barru, with research time from September to November 2019. The population in this study were all employees at the Dinas Pekerjaan Umum dan Penataan ruang Kabupaten Barru as many as 81 people. Sampling of this study was carried out using a saturated sampling technique. The data analysis technique used is multiple linear regression analysis. The results showed that there was an influence of morale, leadership style, and work motivation on the performance of the employees of the Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Barru. There is an influence between work enthusiasm, leadership style and motivation together on the performance of the employees of the Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Barru. The most dominant motivational variable influences the performance of the employees of Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Barru.